PENYAKIT NABI AYUB DALAM AL-QUR’AN MENURUT IBNU KATSIR DAN AL-SAYYID MUHAMMAD BIN ‘ALAWI AL-MALIKI AL-HASANI (Studi Perbandingan Tafsîr al-Qurân al-‘Azhîm dan Jala’ al-Afhâm Syarh Aqîdah al-Awâm) - Faris, Farhan; Nawawi, Abd Muid; Nurbaiti, Nurbaiti (Madani Institute : Jurnal Politik, Hukum, Ekonomi, Pendidikan dan Sosial-Budaya, 2024)
The focus of this research is to analyze the illness of the Prophet Job by comparing the opinions of Ibn Kathir and al-Sayyid Muhammad bin 'Alawi al-Maliki al-Hasani. This research is limited to the interpretation of the Prophet Ayub's illness carried out by Ibnu Kathir in Q.S. al-Anbiyâ'/21: 83 and Q.S. Shâd/38: 41-44, also the opinion of al-Sayyid Muhammad bin 'Alawi al-Maliki al-Hasani in the book Jala' Al-Afhâm Syarh 'Aqîdah al-'Awâm. The type of research used is library research using a comparative study research method between the opinions of Ibn Katsir and al-Sayyid Muhammad bin 'Alawi al-Maliki al-Hasani and supported by other secondary sources such as Tafsîr al-Azhâr and Tafsîr al-Marâgi . It was found in this research that in studying Ibn Kathir's interpretation of the Prophet Ayub's illness in Q.S. al-Anbiyâ'/21: 83 has slight differences with the interpretation of Q.S. Shâd/38: 41. In Q.S. al-Anbiyâ'/21: 83, as a result of the skin disease experienced by the Prophet Job, the flesh of the Prophet Job fell off until nothing remained except his nerves and bones. Then the Prophet Job's illness became very serious, namely the disease that befell him was leprosy which affected his entire body, so that not a single part of his body was safe from this disease, except for his heart and tongue which always recited the remembrance of Allah SWT. In Q.S. Shâd/38: 41, Ibn Kathir even exaggerated in describing the disease that affected the entire body of the Prophet Job so that not a single pore of his body was safe from the disease except only his heart. Meanwhile, al-Sayyid Muhammad bin 'Alawi al-Maliki al-Hasani in the book Jala' al-Afhâm Syarh Aqîdah al-Awwâm comments that the Prophet and Apostle only had mild skin ailments. Al-Maragi indicated that the skin diseases suffered such as eczema, itching, and the like were not contagious and could be cured with artesian water or sulfur water